Passivation Layer and Cathodic Redox Reactions in Sodium‐Ion Batteries Probed by HAXPES1. Issue 1 (22nd December 2015) - Doubaji, Siham; Philippe, Bertrand; Saadoune, Ismael; Gorgoi, Mihaela; Gustafsson, Torbjorn; Solhy, Abderrahim; Valvo, Mario; Rensmo, Håkan; Edström, Kristina
Abstract: The cathode material P2‐Na x Co2/3 Mn2/9 Ni1/9 O2, which could be used in Na‐ion batteries, was investigated through synchrotron‐based hard X‐ray photoelectron spectroscopy (HAXPES). Nondestructive analysis was made through the electrode/electrolyte interface of the first electrochemical cycle to ensure access to information not only on the active material, but also on the passivation layer formed at the electrode surface and referred to as the solid permeable interface (SPI). This investigation clearly shows the role of the SPI and the complexity of the redox reactions. Cobalt, nickel, and manganese are all electrochemically active upon cycling between 4.5 and 2.0 V; all are in the 4+ state at the end of charging. Reduction to Co 3+, Ni 3+, and Mn 3+ occurs upon discharging and, at low potential, there is partial reversible reduction to Co 2+ and Ni 2+ . A thin layer of Na2 CO3 and NaF covers the pristine electrode and reversible dissolution/reformation of these compounds is observed during the first cycle. The salt degradation products in the SPI show a dependence on potential. Phosphates mainly form at the end of the charging cycle (4.5 V), whereas fluorophosphates are produced at the end of discharging (2.0 V). Abstract : Don't stand idly by ! Based on photoelectron spectroscopy results obtained on a synchrotron, the crucial role of the passivation layer present at the surface of a P2‐Na x (Co2/3 Mn2/9 Ni1/9 )O2 cathode for use in Na‐ion batteries is described. This technique also enables the evolution of the oxidation state of the three transition metals to be followed; all are active during electrochemical cycling.